Optimal Skyhook and Groundhook Control for Semiactive Suspension: A Comprehensive Methodology - C. Steven Díaz-Choque; L. C. Félix-Herrán; Ricardo A. Ramírez-Mendoza (Shock and Vibration)
This manuscript establishes a methodology that guides the designers to develop an optimal controller for a semiactive suspension system. The methodology’s processes are generally explained and straightforwardly, so a designer can extrapolate the methodology to a specific problem. Furthermore, this research presents an optimal control strategy for a semiactive control applied to a quarter vehicle model as an example of using the methodology. A particular interest is made in the advantages of such a simple synthesis and in the compromises that must be done in skyhook and groundhook control law applications. This manuscript exposes a logical and straightforward approach for choosing the controllers’ design parameters; also, efforts must be made to express precise performance specifications and constraints in the control design. The herein methodology could be relevant in the process design for intelligent suspensions, from one-quarter toward the entire vehicle.